Mobilisation of Stool Land Revenue for the development of local economies: The prospects and challenges. Issue 2 (3rd July 2022) - Pomevor, S. M.
ABSTRACT: Land serves as a source of revenue for development. Using semi-structured interviews and questionnaires, a case study of the Wassa Fiase traditional area was carried out to examine the prospects and challenges for the mobilisation of stool land revenue for the development of communities. The study found out that the land tenure system in the area was dynamic with a lot of governance challenges. The mobilisation of stool land revenue was constrained by inadequate staffing, reliance on manual records, and lack of cooperation from some chiefs. There was also the opportunity for the mobilisation of more revenue; many sources of revenue to be mobilized, the availability of records of land transactions and the opportunity to carry out public education and sensitization. It was recommended that the digitization of land records, provision of sanctions for rent defaulters, and the demarcation of their stool land boundaries would help improve revenue mobilisation.